2021
DOI: 10.1016/j.toxrep.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic safety evaluation of hot-water extract from thinned immature mangos (Mangifera indica ‘Irwin’): 90-days oral toxicity study in rats

Abstract: Graphical abstract Thinned Irwin mango fruits were collected at the immature stage and lyophilized. Hot-water extract from thinned immature mango (TIMEx) had no toxic effect on SD rats given daily oral doses of 500, 1000 or 2500 mg/kg for 90 days. No significant alterations in hematological and serum chemical parameters, urinalysis, food consumption, body weight gain, or absolute and relative organ weights were noted in any group. In both sexes, a daily dose up to 2500 mg/kg body weight indicates a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In this study, the hematology and blood chemistry parameters were selected based on the rat study reported by Tajri H et al [18] . All the animals were kept in a biologic cage and blood samples were collected in the early morning between 7.00 and 9.00AM to reduce biological variation caused by circadian rhythms from all animals at the end of the experiment period under fasting conditions at least for 14 h but allowed access to water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the hematology and blood chemistry parameters were selected based on the rat study reported by Tajri H et al [18] . All the animals were kept in a biologic cage and blood samples were collected in the early morning between 7.00 and 9.00AM to reduce biological variation caused by circadian rhythms from all animals at the end of the experiment period under fasting conditions at least for 14 h but allowed access to water ad libitum.…”
Section: Methodsmentioning
confidence: 99%